What parents want to know about caring for their preterm infant: A longitudinal descriptive study. Issue 11 (November 2021) - Furtak, Stephannie L.; Gay, Caryl L.; Kriz, Rebecca M.; Bisgaard, Robin; Bolick, Scott C.; Lothe, Brittany; Cormier, Diana M.; Joe, Priscilla; Sasinski, Juliet K.; Kim, Jae H.; Lin, Carol K.; Sun, Yao; et al.
Highlights: Parents sought information about their preterm infant's medical course (respiratory conditions and management) and feeding. Parents learned feeding and care skills throughout and specific skills for their infant's condition later in the NICU stay. Parent learning needs and number of skills learned varied over the NICU stay and by parent age, gender, and education. Abstract: Objectives: To describe the characteristics of parent knowledge needs and skill acquisition over the course of their infant's neonatal intensive care unit hospitalization. Methods: 148 parents/guardians of infants ≤33 week gestation enrolled during the usual care phase of a multi-site quasi-experimental study, completing weekly surveys about their learning needs for the coming week and skills learned in the past week. Results: The topics of most interest or concern for parents included feeding their infant and their infant's medical course. Knowledge needs varied by phase of hospitalization (early, middle, late) and by parent age, prior parenting experience, infant gestational age and hospital length of stay. The most common skills learned related to feeding and basic infant care. The number of skills parents reported learning each week varied by parent age, gender, and education. Conclusions: Parents of preterm infants expressed specific learning needs and acquisition of skills that varied over the course of the hospitalization and by parent and infant characteristics. Practice implications: The findings can be used to improve parent learning experiences so that they can become full partners in their infant's caregiving and are better prepared to care for their infant after discharge. Study registration: ClinicalTrials.gov, ID NCT03418870.